Altitude-dependent Variation in Antibacterial Properties of Red Ginger (Zingiber officinale var. rubrum): Implications for Natural Anti-Salmonella Agents - Widyastuti, Dyah Ayu; Nuringtyas, Tri Rini; Rohman, Abdul; Santosa, Djoko (Advance Sustainable Science Engineering and Technology, 2026)
Red ginger contains diverse bioactive compounds with strong antioxidant and antibacterial activities. This study investigated the influence of growth location on the anti-Salmonella activity of red ginger extracts from seven regions in Java, Indonesia. The fractions were analyzed for total phenolic and flavonoid contents, as well as antioxidant capacity using DPPH and FRAP assays. Antibacterial activity was assessed against Salmonella using the Kirby-Bauer disk diffusion method. Results showed that methanol and ethyl acetate fractions exhibited the highest phenolic and flavonoid contents, while the chloroform fraction demonstrated the strongest radical scavenging activity. Extracts from Bumiaji and Lendah displayed the most potent anti-Salmonella activity (inhibition zone: 10.08 to 18.00 mm). These findings highlight that altitude and solvent polarity influence red ginger bioactivity, supporting its potential as a natural antibacterial source.